TYPOLOGIES OF TRAVELER BEHAVIOR IN CONTEMPORARY UKRAINIAN LITERATURE OF THE EARLY 21ST CENTURY - Розінкевич, Наталія (SWorldJournal, 2025)
The article is devoted to the study of the typology of traveler-heroes in contemporary Ukrainian prose of the early 21st century. Travel prose is conceptualized as a form of interaction between the individual and space, culture, memory, and identity, refl